Analisis Anggaran Pemerintah (APBN dan APBN-P) dalam Perspektif Demokrasi Multipartai dan Koalisi - Sitepu, Badikenita (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
Democratic system change in Indonesia resulted in a change of political system and economy of Indonesia. Changes in the political system was also followed by the country’s financial sector reform (or budget) in the process of change towards prosperity residents better. Using time series data from 1982 to 2011, this study found that the coalition is formed to have a positive and significant effect on the level of budget revenues in the state budget approval and the state budget, as well as the approval of the budget at the level of state budget. The Coalition does not have influence on the level of approval signifcant budget on state budget. The number of political parties only affect the level of budget revenues in the state budget approval. The level of tax agreements have a significant impact on the level of state budget approval and the state budget. Revenue budget approval rate has a significant influence on the level of approval of both the state budget expenditures and state budget.